Immunological composition of human milk before and during subclinical and clinical mastitis - Castro-Navarro, Irma; Pace, Ryan M.; Williams, Janet E.; Pace, Christina D. W.; Kaur, Harpreet; Piaskowski, Julia; Aragón, Alberto; Rodríguez, Juan M.; McGuire, Mark A.; Fernandez, Leonides; McGuire, Michelle K. (Frontiers in Immunology, 2025)
Mastitis, an inflammatory condition affecting more than 25% of breastfeeding women, is usually associated with reduced milk secretion, pain, and discomfort, which often leads to early cessation of breastfeeding. Although the etiology of mastitis is multifactorial, a pro-inflammatory state of the mammary gland might be a risk factor. However, changes in milk composition, and specifically in the milk immune profile, prior to and during mastitis have not been well described. To help close this research gap, we documented the immune profiles of milk produced by both breasts of 10 women experiencing clinical (CM) and 8 women experiencing subclinical (SCM) mastitis during the week of sign/symptom development as well as the week prior and compared them with milk produced by 14 healthy controls. CM was defined as having signs/symptoms of mastitis, whereas SCM was presumed if the participant did not have signs/symptoms of CM, but her milk had a somatic cell count >400,000 cell/mL and/or sodium-to-potassium (Na/K) ratio >1.0. Concentration of 36 immune factors (including immunoglobulins, cytokines, chemokines, and growth factors) was quantified via immunoassays. Milk produced by women who developed CM had distinct immune profiles the week prior to diagnosis, particularly elevated concentrations of pro-inflammatory cytokine IL-1β and regulatory cytokines IL-2, IL-4 and IL-10. In contrast, immune profiles in milk produced by women with SCM did not differ from that produced by healthy women or those with CM the week prior to mastitis onset. Once mastitis appeared, marked changes in milk’s immune profile were observed in both CM and SCM groups. CM was characterized by elevated concentrations of 27 compounds, including pro-inflammatory cytokines (IL-1β, IL-1ra, and TNFα) and chemokines (including IL-8, eotaxin, IP-10, MCP-1, MIP1α, and MIP1β), compared to healthy controls. Milk’s immune profile during SCM was intermediate, showing higher levels of IL-6, IFNγ, and MCP-1 compared to healthy controls, suggesting a milder, more controlled immune response compared to CM. Only milk produced by the mastitis-affected breast had altered immune profiles. Further research is needed to determine if these differences in milk’s immune profiles can be used to improve mastitis risk prediction prior to onset of symptoms.